Thermoplastic compositions, molded parts made therefrom and their use in automotive and electrical and electronic applications
By optimizing the ratio of semiaromatic copolyamide and reinforcement in the thermoplastic composition, the mechanical properties and foaming problems of thermoplastic compositions in the automotive and electronic fields in the prior art are solved, and high tensile strength and breaking extension are achieved Longitudinal and impact resistance, while reducing the risk of bubbles in lead-free reflow soldering.
Patent Information
- Application Number
- CN202210639800.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-12-08
- Filing Date
- 2017-12-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2037-12-08
AI Technical Summary
The existing thermoplastic compositions are difficult to meet the requirements of high tensile strength, elongation of break and impact resistance in the automotive and electronics fields, and there are bubble problems, especially in the lead-free reflow welding step.
Using a thermoplastic composition containing a specific molar ratio of semiaromatic copolyamide and reinforcement, the ratio of diamine and dicarboxylic acid and viscosity values are optimized, combined with glass fiber or carbon fiber reinforcement, to prepare high mechanical properties and low ease Foamy plastic parts.
It realizes the improvement of tensile strength, elongation of break and impact resistance without using impact modifiers or changing the enhancement dose, while reducing the susceptibility of plastic parts to high temperatures, satisfying automobiles and electronics Strict mechanical performance requirements in the field.
Smart Images

Figure BDA0003683369040000101 
Figure BDA0003683369040000121 
Figure BDA0003683369040000131
Abstract
Description
[0001] The present invention relates to a thermoplastic composition comprising a semiaromatic copolyamide and a reinforcing agent. The present invention also relates to a plastic part made from the thermoplastic composition. The present invention also relates to a motor vehicle comprising a structural part made from the thermoplastic composition and an electrical assembly comprising a plastic component made from the thermoplastic composition.
[0002] Plastic parts made of reinforced thermoplastic compositions are widely used in automotive applications and electrical and electronic applications. A widely used material in plastic parts for these applications is a reinforced thermoplastic composition, i.e. a thermoplastic composition comprising a thermoplastic polymer (such as polyester or polyamide) and a reinforcing agent. Examples of such polymers are aliphatic polyamides (such as PA-46), semi-crystalline semi-aromatic polyamides (PPA) based on monomers comprising aromatic monomers such as terephthalic acid and diamines, and polycyclohexane dimethyl terephthalate (PCT) (a thermoplastic polyester formed by the polycondensation reaction of terephthalic acid and cyclohexanedimethanol). For example, prior art PPAs are described in WO-2007085406-A1. Using compositions based on PCT, higher elongations can be achieved compared to similar PPA compositions, for example when impact modifiers are used, but typically tensile strength is lower and impact resistance also remains lower. A typical solution to increase elongation at break is to use an impact modifier, but this is usually at the expense of tensile strength. Vice versa, tensile strength can be increased, for example by increasing the amount of reinforcing agent, but this is usually at the expense of elongation at break and may further lead to a reduction in flow properties, resulting in incomplete filling of the mold during injection, among other problems.
[0003] In the automotive field, there is a systematic trend for metal parts to be replaced by plastic materials. This tends to include metal substitutes for engine parts and structural parts close to the engine. For such applications, the requirements for several properties (including mechanical properties, such as high tensile strength and impact resistance) have become more stringent. In the field of electronic plastic components, there is a systematic trend of further miniaturization, resulting in thinner parts, such as parts with a thickness of 1 mm or less. In addition, the requirements for mechanical properties (especially the combination of high tensile strength and high elongation at break) have become more critical, especially for those parts. In this article, plastic components generally have parts with higher thickness to properly strengthen the components as support for thinner parts. When such components are used in the method for manufacturing an assembly of surface-mounted electronic components, wherein the plastic components are subjected to a step including lead-free reflow soldering, the occurrence of blistering should be avoided (see, for example, the JEDEC MSL standard, i.e., the standard for moisture sensitivity levels of the Joint Electronic Device Engineering Committee). Blistering not only deteriorates the appearance of the component, but also damages the mechanical integrity. For parts with higher thickness (e.g., 2-3 mm), it is usually more difficult to avoid blistering than for parts with lower thickness (less than 1 mm).
[0004] Currently used materials have limitations with respect to these requirements, which explains the need for materials with better properties.
[0005] One object of the present invention is therefore to provide a reinforced thermoplastic composition having an improved combination of mechanical properties compared to the corresponding PPA and PCT based compositions cited, more particularly exhibiting a combination of high tensile strength and high elongation at break, combined with high impact strength.
[0006] Another object is to provide reinforced thermoplastic compositions and parts made therefrom which have an improved combination of mechanical properties compared to the corresponding PPA- and PCT-based compositions cited, more particularly showing a combination of high tensile strength and high elongation at break, combined with high impact strength and reduced susceptibility to blistering.
[0007] The first object is achieved by a thermoplastic composition according to the invention according to claim 1 , comprising (A) a semiaromatic copolyamide, and (B) a reinforcing agent.
[0008] One embodiment of the present invention relates to structural parts for automotive and E&E applications, made from the thermoplastic composition according to the invention according to claim 1 .
[0009] The second object is achieved by a component for electronic equipment, which comprises a molded part made of a composition comprising (A) a semiaromatic copolyamide as claimed in claim 1, and (B) a reinforcing agent.
[0010] A particular embodiment thereof relates to an electronic device comprising an assembly of components assembled using surface mount technology, said components having been subjected to a lead-free soldering step.
[0011] In this context, the semiaromatic copolyamide (component A) comprises repeating units derived from a diamine and a dicarboxylic acid or a salt thereof or any mixture thereof, wherein
[0012] a. diamine (in this context it is understood that the repeating units are derived from diamines and / or their salts) consists of 80-100 mol % of a mixture of tetramethylenediamine and hexamethylenediamine or 80-100 mol % of a mixture of pentamethylenediamine and hexamethylenediamine, and 0-20 mol % of one or more other diamines, wherein the mol % is relative to the total molar amount of diamines;
[0013] b. dicarboxylic acids (understood herein as repeating units derived from dicarboxylic acids and / or salts thereof) consisting of 90-100 mol % of terephthalic acid, 0-10 mol % of one or more other aromatic dicarboxylic acids and 0-2 mol % of aliphatic dicarboxylic acids, wherein the mol % are relative to the total molar amount of dicarboxylic acids;
[0014] c. the copolyamide comprises 0-2 mol % of repeating units derived from other monomer components, the repeating units comprising 0-0.1 mol % of branching units, wherein the mol % is relative to the total molar amount of diamine, dicarboxylic acid and other monomer components; and
[0015] d. The viscosity number (VN) of the copolyamide is at least 100 ml / g.
[0016] The effect of the composition according to the invention comprising the combination of the copolyamide and the reinforcing agent is that the combination of all three properties, namely tensile strength, elongation at break and impact resistance, is improved relative to comparable materials based on the other polymers mentioned above, using the same or similar reinforcing agent package. This is very surprising, since this effect can also be obtained without using an impact modifier or changing the amount of reinforcing agent.
[0017] The copolyamide in the composition according to the invention has a viscosity number (VN) of at least 100 ml / g. The viscosity number (VN) is measured in sulfuric acid at 0.5% by weight by the method according to ISO 307, fourth edition. Preferably, the viscosity number (VN) is at least 110 ml / g, more preferably at least 120 ml / g. The advantage of higher viscosity numbers (VN) is that both the tensile strength and the elongation at break are further increased.
[0018] The semi-aromatic copolyamide used in the composition according to the present invention is a substantially linear copolyamide, which contains a small amount of branched components (if any). Typically, the preparation of high molecular weight polyamides involves the use of branching agents, or occurs due to the formation of branched components during the polymerization process. Typically, monofunctional monomers such as monoamines or monocarboxylic acids are used in combination with branching agents to prevent gelation. The semi-aromatic copolyamide comprises repeating units derived from diamines and dicarboxylic acids, or salts thereof, or any mixture thereof. The expression "salts thereof" should be understood as diamine salts and dicarboxylates. The expression "any mixture thereof" should be understood as a mixture of diamines and their salts (any one or more diamine salts) and a mixture of dicarboxylic acids and their salts (any one or more dicarboxylates). Therefore, the semi-aromatic copolyamide used in the composition according to the present invention can be prepared with a small amount of monofunctional monomers (if any). The semi-aromatic copolyamide used in the present invention can be prepared by direct solid-state polymerization, starting from a solid salt component and optionally other components, while keeping the diamine / dicarboxylic acid (salt) ratio close to 1 during the polymerization process. Higher viscosity numbers (VN) can be obtained by using longer polymerization times and using suitable polycondensation catalysts.
[0019] The solid salt component is a salt of a diamine and a salt of a dicarboxylic acid. The solid salt component may be a salt of tetramethylenediamine, a salt of hexamethylenediamine and a salt of terephthalic acid, such as tetramethylenediammonium terephthalate and hexamethylenediammonium terephthalate, and optionally other components, or a salt of pentamethylenediamine, a salt of hexamethylenediamine and a salt of terephthalic acid, such as pentamethylenediammonium terephthalate and hexamethylenediammonium terephthalate, and optionally other components.
[0020] Such semiaromatic copolyamides are described in WO200125311, which mainly contain repeating units based on tetramethylenediamine and hexamethylenediamine and terephthalic acid, and therefore mainly contain tetramethylene terephthalate (4T) and hexamethylene terephthalate (6T) repeating units. The copolyamides are prepared herein by a two-step process, wherein in a first step, a melt phase is applied, or an aqueous solution of tetramethylenediamine, hexamethylenediamine, terephthalic acid in water is prepared, heated and flashed, resulting in the formation of a solid product of a prepolymer, followed by a second step, wherein the prepolymer is further polymerized to obtain the copolyamide. The polymers obtained by the solution process as described in the examples have typical RSV values of 1.35 and 1.54. The VN values of these polyamides are 32 ml / g and 49 ml / g, respectively. Although it is mentioned that higher relative viscosities (higher than, for example, 2, corresponding to a VN of 90 ml / g) can be obtained by selecting other conditions or different methods, no indication of such conditions is given. Furthermore, reprocessing experiments of WO200125311 yielded polymers with RSVs well below 2.
[0021] In WO200125311-A1, it is mentioned that the mechanical properties are well maintained at high temperatures, or that the mechanical properties at high temperatures do not decrease too much with different variations of the composition. The inventors of the present invention have observed that in the VN range of 50-90 ml / g, more particularly 70-90 ml / g, the mechanical properties of tensile strength and elongation at break are almost unchanged, while there is a significant improvement in the mechanical properties when using the composition according to the present invention.
[0022] The diamine is preferably composed of a mixture of 90-100 mol % of tetramethylenediamine and hexamethylenediamine as the main diamine component, or a mixture of 90-100 mol % of pentamethylenediamine and hexamethylenediamine, and 0-10 mol % of one or more other diamines, the mol % being relative to the total molar amount of the diamine. More preferably, a mixture of tetramethylenediamine and hexamethylenediamine is used for the main diamine component, and its total amount is in the range of 95-100 mol %, and the amount of one or more other diamines is in the range of 0-5 mol %, the mol % being relative to the total molar amount of the diamine. The advantage of a lower amount of other diamines is that better mechanical properties are achieved.
[0023] The other diamines herein can be any diamines that can be copolymerized with tetramethylenediamine and hexamethylenediamine and terephthalic acid, or with pentamethylenediamine and hexamethylenediamine and terephthalic acid. The type and amount of such other diamines are appropriately optimized to maintain the desired mechanical properties. Examples of suitable diamines that can be copolymerized with tetramethylenediamine and hexamethylenediamine and terephthalic acid are pentamethylenediamine and linear aliphatic diamines H2N(CH2)xNH2, where x=7-24. Examples of suitable diamines that can be copolymerized with pentamethylenediamine and hexamethylenediamine and terephthalic acid are tetramethylenediamine and linear aliphatic diamines H2N(CH2)xNH2, where x=7-24. Other other diamines that can be copolymerized with either of the two mixtures of the main diamine components include aromatic diamines, cycloaliphatic diamines, and branched diamines. Examples thereof are meta-xylylenediamine, isophoronediamine, 2-methylpentamethylenediamine and trimethylhexamethylenediamine. If used, aromatic diamines, cycloaliphatic diamines and branched diamines are preferably used in a total amount of less than 5 mol %, preferably 0 to 3 mol %.
[0024] In the thermoplastic composition according to the present invention, the diamine preferably comprises tetramethylenediamine and hexamethylenediamine as the main diamine components. In this context, the diamine appropriately comprises tetramethylenediamine and hexamethylenediamine in a molar ratio of 15:85-70:30, preferably 20:80-60:40, more preferably 30:70-50:50. The advantage is that the composition shows better melt processing.
[0025] Similarly, the copolyamide in the thermoplastic composition according to the present invention comprises tetramethylene terephthalamide units (4T) and hexamethylene terephthalamide units (6T) in a molar ratio of 15:85 to 70:30, preferably 20:80 to 60:40, more preferably 30:70 to 50:50.
[0026] The aromatic dicarboxylic acid in the copolyamide mainly comprises terephthalic acid. Preferably, the aromatic dicarboxylic acid comprises at least 95 mol %, preferably 98-100 mol % of terephthalic acid relative to the total molar amount of dicarboxylic acid. The effect is that the composition has a higher hardness at high temperature, while the elongation at break remains at a good level.
[0027] In another preferred embodiment of the present invention, the aromatic dicarboxylic acid consists of 95-100 mol % of terephthalic acid, 0-5 mol % of one or more other aromatic dicarboxylic acids and 0-1 mol % of aliphatic dicarboxylic acids, relative to the total molar amount of dicarboxylic acids.
[0028] In another preferred embodiment, the copolyamide consists of repeating units derived from 95-100 mol % of tetramethylenediamine, hexamethylenediamine and terephthalic acid and 0-5 mol % of other monomers, relative to the total amount of tetramethylenediamine, hexamethylenediamine, terephthalic acid and other monomers.
[0029] The thermoplastic composition according to the invention suitably comprises
[0030] (A) 30 to 90% by weight of a semiaromatic copolyamide, and
[0031] (B) 10-70 wt% reinforcing agent
[0032] The weight percentage (wt %) is relative to the total weight of the composition.
[0033] Preferably, the thermoplastic composition comprises
[0034] (A) 40 to 80% by weight of a semiaromatic copolyamide, and
[0035] (B) 20-60 wt % of a reinforcing agent;
[0036] The weight percentage (wt %) is relative to the total weight of the composition.
[0037] The reinforcing agent in the composition can be any common filler or fiber for reinforcing the thermoplastic polymer composition. In this article, various fibers and fillers can be used. Examples of such fillers include, but are not limited to, silicon dioxide, metasilicate, aluminum oxide, talc, diatomaceous earth, clay, kaolin, quartz, glass, mica, titanium dioxide, molybdenum disulfide, gypsum, iron oxide, zinc oxide, powdered polytetrafluoroethylene, montmorillonite, calcium carbonate, glass powder and glass beads. For reinforcing fibers, for example, aromatic fibers and inorganic fibers can be used. Preferably, inorganic fibers are used. Examples thereof are glass fibers, carbon fibers, boron fibers, ceramic fibers, and whiskers of potassium titanate and wollastonite.
[0038] Preferably, the reinforcing agent comprises or even consists of glass fibers or carbon fibers or a combination thereof. More preferably, glass fibers are used. These glass fibers can have various compositions and shapes, for example, S-glass, E-glass and basalt glass, as well as round glass and flat glass fibers.
[0039] In one embodiment of the invention, the composition comprises or even consists of the following components:
[0040] (A) 30 to 90% by weight, preferably 40 to 80% by weight, of the semiaromatic copolyamide of the invention, and
[0041] (B) 10-70 wt %, preferably 20-60 wt % of an inorganic filler, or an inorganic fiber, or a combination thereof;
[0042] The weight percentage (wt %) is relative to the total weight of the composition.
[0043] In another embodiment, the composition comprises or even consists of the following components:
[0044] (A) 30 to 90% by weight, preferably 40 to 80% by weight, of the semiaromatic copolyamide of the invention, and
[0045] (B) 10-70 wt %, preferably 20-60 wt % of glass fibers, or carbon fibers, or a combination thereof;
[0046] The weight percentage (wt %) is relative to the total weight of the composition.
[0047] In addition to copolyamide and reinforcing filler, the thermoplastic composition according to the present invention may optionally contain one or more additional components. Suitably, such additional one or more components are selected from common additives, such as stabilizers, colorants, processing aids (such as release agents and lubricants), reagents and flame retardants for improving impact resistance. Such thermoplastic compositions containing copolyamides may also optionally contain polymers other than polyamides. However, their amount is preferably limited so as not to deteriorate mechanical properties.
[0048] Suitably, the amount of one or more additional components is 0-30% by weight, preferably 0-20% by weight, relative to the total weight of the composition. Suitably, the amount of other polymers is 0-15% by weight, preferably 0-10% by weight, more preferably 0-5% by weight, relative to the total weight of the composition.
[0049] The thermoplastic composition according to the present invention has remarkable mechanical properties, which contribute to better performance of molded parts made therefrom in various applications. Preferably, the composition has a tensile strength (TS) of at least 200 MPa, more preferably at least 210 MPa, or an elongation at break (EaB) of at least 2.3%, more preferably at least 2.5%, or any combination thereof. In this context, TS and EaB are measured by the method according to ISO 527 / 1 at 23°C at a tensile speed of 5 mm / min on a test bar conforming to ISO527 1A type and having a thickness of 4 mm.
[0050] The thermoplastic composition according to the invention is very suitable for forming products from the melt, in particular by injection molding. Products obtained by using the plastic composition according to the invention are, for example, automotive parts, and electrical and electronic components. The molded parts are advantageously structural parts for motor vehicles or electronic equipment, or plastic components for electrical assemblies.
[0051] Examples of structural components for motor vehicles are engine mounts, structural oil pans, shift forks, transaxles, thermal management modules, crankshaft covers, timing chain covers, bearing cages.
[0052] Examples of structural components for electronic devices are housings, frames, intermediate frames and reinforcements, such as for laptop computers and mobile phones.
[0053] Specifically, structural components for electrical and electronic components are connectors, terminal blocks, pin headers, lead frames, switches, relays, capacitors, resistors, camera modules.
[0054] Typically, plastic components are used as part of electronic assemblies that are assembled on printed circuit boards (PCBs) through a lead-free reflow soldering process.
[0055] Examples of plastic components used in electrical assemblies are connectors, such as those used in automotive applications, connectors and other parts that must pass through a reflow process.
[0056] The invention also relates to a molded plastic part made of (understood herein as consisting of) a thermoplastic composition according to the invention or any specific or preferred embodiment thereof. The advantages thereof are those described above for the thermoplastic composition. Preferably, the molded plastic part is a structural part for a motor vehicle or a plastic component for an electrical assembly, more preferably a plastic component having a portion with a thickness of at least 1.6 mm. Despite the presence of thicker portions, the latter component has the advantage that it has an improved resistance to blistering during lead soldering.
[0057] The invention also relates to a motor vehicle comprising a structural component according to the invention. The effect is improved mechanical properties as described above. Another advantage is that the high temperature mechanical properties do not deteriorate as when using impact modifiers, while the structural component still has high strength and high elongation.
[0058] The invention also relates to an electronic device comprising a housing, a frame or a reinforcement made of (understood herein as consisting of) a composition according to the invention. The electronic device is, for example, a laptop or a mobile phone. The advantage is that the electronic device can be better protected from damage due to better mechanical properties and improved impact resistance.
[0059] The present invention also relates to an assembly of surface mounted electronic components comprising a plastic component made according to the present invention. The advantage is that the plastic component has not only improved mechanical properties as described above, but also improved blistering properties. This improved blistering property is particularly important for plastic components with relatively high thickness portions when subjected to an assembly process including a lead-free reflow soldering step.
[0060] A preferred embodiment thereof relates to an assembly in which the plastic component has a portion with a thickness of at least 1.6 mm.
[0061] The present invention also relates to a method for preparing an assembly of a surface mounted electronic component, wherein the plastic component according to the present invention or any preferred or specific embodiment thereof is subjected to a step comprising lead-free reflow soldering.
[0062] The present invention is further illustrated by the following examples and comparative experiments.
[0063] Test Method
[0064] Mechanical Testing
[0065] The mechanical properties of tensile strength, elongation at break and tensile modulus were determined in a tensile test according to ISO 527 / 1 at 23° C. and a tensile speed of 5 mm / min according to ISO 527. In this context, test bars according to ISO 527 type 1A and having a thickness of 4 mm were used.
[0066] Blistering performance under reflow soldering conditions
[0067] For the blistering performance under reflow soldering conditions, a large number of samples were conditioned in a humidified box with a predetermined temperature and humidity level. For the embodiments according to the present invention, the following conditioning was used: 168 hours at 85°C and 85% relative humidity (RH). This conditioning was carried out in a climate chamber. At different time intervals, a group of samples (10 in a batch) were taken out of the box, immediately cooled to room temperature under ambient conditions, placed in a reflow oven, and then subjected to the temperature conditions applied by the reflow soldering process. The reflow profile was applied to the samples within one hour after exiting the preconditioning. The so-called Sony reflow profile was used. The typical temperature profile applied is as follows. First, the sample was preheated to a temperature of 140°C after 80 seconds with an average temperature increase of 1.5°C / second, after which the sample was heated more slowly to reach 160°C after 160 seconds from the start. The sample was then heated to 260°C or 270°C (two different experiments were performed at two different temperatures), where the temperature was initially increased at about 6°C / second to reach a temperature of 220°C after 240 seconds from the start, and then at a slower heating rate of 2°C / second to reach a temperature of 260°C (or 270°C) after 290 seconds from the start. Thereafter, the sample was cooled to 140°C within 30 seconds. Ten samples were then taken out of the oven, cooled to room temperature, and tested for the presence or absence of bubbles. For each conditioning period in the humidifying chamber, the percentage of samples in which bubbling occurred was evaluated. The percentage of samples with bubbles was recorded. For each thickness, the reflow process was calibrated for maximum temperatures of 260°C and 270°C, respectively, using thermocouples on plastics and on PCBs (very close to plastic components (connectors), where the temperature of the PCB determines the temperature distribution). Reflow can be performed on small boards or connectors, and different components with different thicknesses can be used. The temperature is measured on the sample and the PCB.
[0068] This process can be performed using a maximum temperature of 260°C or 270°C and must be performed within one hour after conditioning. The humidification condition before reflow soldering is 168 hours at 85°C and 85% RH (relative humidity), and this conditioning is performed in a humidified chamber.
[0069] Determination of viscosity value
[0070] The measurement is carried out according to ISO 307, 4th edition. For the measurement, predried polymer samples are used, the drying of which is carried out at 80° C. for 24 hours under high vacuum (ie less than 50 mbar). The determination of the relative viscosity is carried out in 100 ml of sulfuric acid 96.00±0.15% m / m solvent at a concentration of 0.5 g of polymer at 25.00±0.05° C. The flow times of the solution (t) and the solvent (to) are measured at 25° C. using a DIN-Ubbelohde from Schott (reference number 53020).
[0071] The viscosity value is calculated as follows:
[0072]
[0073] in:
[0074] VN = viscosity value (unit: mL / g)
[0075] t = average flow time of the sample solution in seconds
[0076] t 0 = average flow time of the solvent in seconds
[0077] c = concentration, g / mL (= 0.005)
[0078] raw material
[0079] PCT ThermX CG033: 30% glass fiber reinforced poly(cyclohexane dimethyl terephthalate) for injection molding (from Ticona)
[0080] PCT+IM ThermX CGT033: 30% glass fiber reinforced impact modified poly(cyclohexane dimethyl terephthalate) for injection molding (from Ticona)
[0081] PA-1 PA-4T / 6T / 46 copolymer (from DSM)
[0082] Other Materials:
[0083] Preparation of PA-2 (PA-4T / 6T copolymer)
[0084] 15 kg of 4T / 6T salt (39 / 61 mol / mol) was added to a 50 liter drum dryer. The drum dryer was evacuated to 50 mbar and nitrogen was added and repeated 5 times. The mixture was heated to a temperature of 220 ° C in 5 hours, and then heated to 255 ° C in 15 hours, while the reaction water was left in the drum dryer. Low nitrogen was used to purge during the reaction. The mixture was cooled to 235 ° C in 19 hours, and a mixture of 650g 1,6-hexamethylenediamine, 300g 1,4-butylene diamine and 1.0kg water was added during 7 hours, while maintaining the temperature at 235 ° C. The mixture was reacted for another 29 hours at 235 °. Then a nitrogen stream was added, and the material was cooled to room temperature. A white powder was obtained.
[0085] Preparation of PA-3 (PA-4T / 6T copolymer)
[0086] 15 kg of 4T / 6T salt (39 / 61) and 0.015 kg of sodium hypophosphite monohydrate were added to a 50 liter drum dryer. The drum dryer was evacuated to 50 mbar and nitrogen was added and these steps were repeated 5 times. The mixture was heated to a temperature of 220°C in 5 hours, and then heated to 255°C in 15 hours, while the reaction water was left in the drum dryer. During the reaction, a low nitrogen purge was used. The mixture was cooled to 235°C in 19 hours, and a mixture of 650 g of 1,6-hexamethylenediamine, 300 g of 1,4-butylene diamine and 1.0 kg of water was added during 7 hours, while maintaining the temperature at 235°C. The mixture was reacted for another 29 hours at 235°. Then a nitrogen stream was added, and the material was cooled to room temperature. A polymer was obtained, which was a white powder.
[0087] Preparation of PA-4 (PA-4T / 6T copolymer)
[0088] The preparation of PA-4 was repeated except that the reaction time was increased from 29 hours to 39 hours before starting cooling. The polymer was obtained as a white powder.
[0089] Compounding: Preparation of glass fiber reinforced polyamide compositions
[0090] A polyamide composition based on PA-1, PA-2, PA-3 and PA-4 combined with 30 wt% glass fiber was prepared on a twin-screw extruder using standard molding conditions. In this context, the temperature of the extruded melt is typically about 350-360° C. After melt compounding, the resulting melt is extruded into strands, cooled and cut into pellets.
[0091] Injection molding - Preparation of test bars for mechanical and blister testing
[0092] The above polyamide composition was used to prepare injection molded parts. For injection molding, the material was predried before use by applying the following conditions: the copolyamide was heated to 150°C under a vacuum of 0.02 MPa and kept at this temperature and pressure for 12 hours while passing a nitrogen flow. The predried material was injection molded on an Arburg 5 injection molding machine with a screw diameter of 22 mm. In this article, the temperature of the cylinder wall was set to 345°C and the temperature of the mold was set to 140°C.
[0093] For the test bars used for mechanical testing, a die was used that complies with ISO 527 Type 1A. The thickness of the test bars was 4 mm.
[0094] In order to test the blistering performance under reflow soldering conditions, test bars prepared by injection using a Campus UL injection mold were used. In this paper, Campus UL bars with different thicknesses were prepared as needed for further testing.
[0095] The test results for the compositions and mechanical properties of Comparative Experiments AD and Examples I and II have been collected in Table 1. The blistering results in the reflow soldering simulation test have been collected in Table 2.
[0096] Table 1. Composition and mechanical properties (TM = tensile modulus; TS = tensile strength; EaB = elongation at break)
[0097]
[0098] The above results show that the compositions according to the invention (EX-I and EX-II) combine high elongation at break (EaB) with high tensile strength and high impact strength. The EaB is comparable to that of CE-B (based on impact-modified PCT), while having much higher TS and IR. Both EX-I and EX-II have higher TS, EaB and impact strength compared to CE-C (PPA-1) and CE-D. More specifically, the performance of EX-I is much better than that of CE-C; while the two copolyamides have different compositions, their viscosity values are roughly the same.
[0099] Table 2. Reflow results after conditioning at 85°C / 85%RH for 168 hours (blistering performance after reflow; percentage of failure rate of test bars showing bubbles: 0% is 0% bubbles, all passed; 100% is 100% bubbles, all failed)
[0100]
[0101] The above results show that the compositions according to the invention (EX-I and EX-II) show significantly improved blistering properties over the entire thickness range of 0-3.2 mm and comply with the JEDEC requirements (Sony curve T up to 260°C / 270°C; after conditioning for 168 hours at 85°C / 85% RH). This is in contrast to comparative experiments C and B, which failed in all tests above a sample thickness of 1.2 mm. When tested at T up to 270°C, EX-I only becomes critical at a maximum thickness of 3.2 mm, while EX-II still passes over the entire range. Under these conditions, CE-B and CE-C already fail at thicknesses above 0.8 mm. In addition, CE-B already shows partial melting.
[0102] In order to further illustrate certain aspects of the present invention, the present invention also specifically provides the following non-limiting embodiments:
[0103] Embodiment 1. A thermoplastic composition comprising
[0104] (A) a semiaromatic copolyamide comprising repeating units derived from a diamine and a dicarboxylic acid or a salt thereof or any mixture thereof, wherein
[0105] a. The diamine is composed of 80-100 mol % of a mixture of tetramethylenediamine and hexamethylenediamine or 80-100 mol % of a mixture of pentamethylenediamine and hexamethylenediamine, and 0-20 mol % of one or more other diamines, wherein the mol % is relative to the total molar amount of the diamine;
[0106] b. The dicarboxylic acid is composed of 90-100 mol % of terephthalic acid, 0-10 mol % of one or more other aromatic dicarboxylic acids and 0-2 mol % of aliphatic dicarboxylic acids, wherein the mol % is relative to the total molar amount of the dicarboxylic acid;
[0107] c. The copolyamide comprises 0-2 mol % of repeating units derived from other monomer components, wherein the repeating units include 0-0.1 mol % of branching units, wherein the mol % is relative to the total molar amount of diamine, dicarboxylic acid and other monomer components;
[0108] d. the viscosity number (VN) of the copolyamide is at least 100 ml / g; VN is measured by a method according to ISO 307, 4th edition, at 25° C. in sulfuric acid at 0.5 wt. %; and
[0109] (B) Enhancer.
[0110] Embodiment 2. A thermoplastic composition according to embodiment 1, wherein the diamine consists of 90-100 mol % of a mixture of tetramethylenediamine and hexamethylenediamine, or 90-100 mol % of a mixture of pentamethylenediamine and hexamethylenediamine, and 0-10 mol of the one or more other diamines, the mol % being relative to the total molar amount of the diamines.
[0111] Embodiment 3. The thermoplastic composition of embodiment 1 or 2, wherein the diamine comprises tetramethylenediamine and hexamethylenediamine in a molar ratio of 15:85 to 70:30.
[0112] Embodiment 4. The thermoplastic composition of any of embodiments 1-3, wherein the aromatic dicarboxylic acid comprises at least 95 mol % of terephthalic acid, the mol % being relative to the total moles of the dicarboxylic acid.
[0113] Embodiment 5. The thermoplastic composition according to any one of embodiments 1-4, wherein the aromatic dicarboxylic acid consists of 95-100 mol % of terephthalic acid, 0-5 mol % of one or more other aromatic dicarboxylic acids, and 0-1 mol % of aliphatic dicarboxylic acids, the mol % being relative to the total molar amount of the dicarboxylic acids.
[0114] Embodiment 6. The thermoplastic composition of any one of embodiments 1-5, wherein the copolyamide is composed of repeating units derived from 95-100 mol % of tetramethylenediamine, hexamethylenediamine, and terephthalic acid, and 0-5 mol % of one or more other monomers, the mol % being relative to the total amount of tetramethylenediamine, hexamethylenediamine, terephthalic acid, and other monomers.
[0115] Embodiment 7. The thermoplastic composition according to any one of embodiments 1-6, wherein the composition comprises
[0116] (A) 30 to 90 wt.% of said semiaromatic copolyamide, and
[0117] (B) 10-70 wt % of the reinforcing agent;
[0118] The weight percentage (wt %) is relative to the total weight of the composition.
[0119] Embodiment 8. The thermoplastic composition according to any one of embodiments 1-6, wherein the composition comprises
[0120] (A) 30 to 90 wt.% of said semiaromatic copolyamide, and
[0121] (B) 10-70 wt % of glass fiber, or carbon fiber, or a combination thereof;
[0122] The weight percentage (wt %) is relative to the total weight of the composition.
[0123] Embodiment 9. The thermoplastic composition of any of embodiments 1-8, wherein the composition comprises one or more additional components.
[0124] Embodiment 10. The thermoplastic composition of any one of embodiments 1-9, wherein the viscosity value is at least 110 ml / g, or wherein the tensile strength is at least 200 MPa, or the elongation at break (EaB) is at least 2.3%, or any combination thereof, wherein
[0125] - the viscosity value is measured by the method according to ISO 307 4th edition at 25°C in sulfuric acid at 0.5% by weight; and
[0126] The tensile strength and elongation at break are measured by the method according to ISO 527 / 1 at 23°C with a tensile speed of 5 mm / min on test bars conforming to ISO 527 Type 1A and having a thickness of 4 mm.
[0127] Embodiment 11. A molded plastic part made from the thermoplastic composition defined in any one of embodiments 1-10.
[0128] Embodiment 12. The molded part of embodiment 11, wherein the molded part is a structural part for a motor vehicle or a plastic component for an electrical assembly.
[0129] Embodiment 13. A motor vehicle comprising the structural component according to embodiment 12.
[0130] Embodiment 14. An electronic device comprising an assembly of surface mounted electronic components comprising the plastic component according to Embodiment 11.
[0131] Embodiment 15. The electronic device of embodiment 14, wherein the plastic component has at least a portion having a thickness of at least 1.6 mm.
[0132] Embodiment 16. A method for preparing an assembly of surface mounted electronic components, wherein the plastic component defined in Embodiment 12 is subjected to a process step including lead-free reflow soldering.
Claims
1. A method for preparing a thermoplastic composition, the thermoplastic composition comprising (A) a semiaromatic copolyamide comprising repeating units derived from a diamine and a dicarboxylic acid or a salt thereof or any mixture thereof, wherein a. The diamine is composed of 80-100 mol % of a mixture of tetramethylenediamine and hexamethylenediamine or 80-100 mol % of a mixture of pentamethylenediamine and hexamethylenediamine, and 0-20 mol % of one or more other diamines, wherein the mol % is relative to the total molar amount of the diamine; b. The dicarboxylic acid is composed of 90-100 mol% of terephthalic acid, 0-10 mol% of one or more other aromatic dicarboxylic acids and 0-2 mol% of aliphatic dicarboxylic acids, wherein the mol% is relative to the total molar amount of the dicarboxylic acid; c. The copolyamide comprises 0-2 mol % of repeating units derived from other monomer components, the repeating units comprising 0-0.1 mol % of branching units, wherein the mol % is relative to the total molar amount of diamine, dicarboxylic acid and other monomer components; d. the copolyamide has a viscosity value VN of at least 100 ml / g; VN is measured by a method according to ISO 307, 4th edition, at 25° C. in sulfuric acid at 0.5 wt %; and (B) enhancers, The method comprises obtaining the semiaromatic copolyamide by direct solid-state polymerization of a solid salt component, which is a salt of a diamine and a dicarboxylic acid, and optionally other components.
2. The method according to claim 1, wherein the diamine is composed of 90-100 mol % of a mixture of tetramethylenediamine and hexamethylenediamine, or 90-100 mol % of a mixture of pentamethylenediamine and hexamethylenediamine, and 0-10 mol of the one or more other diamines, the mol % being relative to the total molar amount of the diamine.
3. The method according to claim 1 or 2, wherein the diamine comprises tetramethylenediamine and hexamethylenediamine in a molar ratio of 15:85 to 70:
30.
4. The process according to claim 1 or 2, wherein the aromatic dicarboxylic acid comprises at least 95 mol % of terephthalic acid, the mol % being relative to the total molar amount of the dicarboxylic acid.
5. The process according to claim 1 or 2, wherein the aromatic dicarboxylic acid consists of 95-100 mol % of terephthalic acid, 0-5 mol % of one or more other aromatic dicarboxylic acids and 0-1 mol % of aliphatic dicarboxylic acids, the mol % being relative to the total molar amount of the dicarboxylic acids.
6. The method according to claim 1 or 2, wherein the copolyamide consists of repeating units derived from 95-100 mol % of tetramethylenediamine, hexamethylenediamine and terephthalic acid, and 0-5 mol % of one or more other monomers, the mol % being relative to the total amount of tetramethylenediamine, hexamethylenediamine, terephthalic acid and other monomers.
7. The method according to claim 1 or 2, wherein the composition comprises (A) 30-90 wt% of said semiaromatic copolyamide, and (B) 10-70 wt % of the reinforcing agent; The weight % is relative to the total weight of the composition.
8. The method according to claim 1 or 2, wherein the composition comprises (A) 30-90 wt% of said semiaromatic copolyamide, and (B) 10-70 wt% of glass fiber, or carbon fiber, or a combination thereof; The weight % is relative to the total weight of the composition.
9. The method of claim 1 or 2, wherein the composition comprises one or more additional components.
10. The method according to claim 1 or 2, wherein the viscosity value is at least 110 ml / g, or wherein the tensile strength is at least 200 MPa, or the elongation at break is at least 2.3%, or any combination thereof, wherein - the viscosity value is measured by the method according to ISO 307 4th edition at 0.5 wt% in sulfuric acid at 25°C; and - The tensile strength and elongation at break are measured by the method according to ISO 527 / 1 at 23°C at a tensile speed of 5 mm / min on test bars conforming to ISO 527 Type 1A and having a thickness of 4 mm.
11. A molded plastic part made from a thermoplastic composition prepared by the process of any one of claims 1-2 and 4-10.
12. The molded plastic part according to claim 11, wherein the molded plastic part is a structural part for a motor vehicle or a plastic component for an electrical assembly.
13. A motor vehicle comprising the molded plastic part according to claim 12, wherein the molded plastic part is a structural part for a motor vehicle.
14. An electronic device comprising an assembly of surface mounted electronic components comprising the molded plastic part according to claim 12, wherein the molded plastic part is a plastic component for an electrical assembly.
15. The electronic device according to claim 14, wherein the plastic component has at least a portion having a thickness of at least 1.6 mm.
16. A method of preparing an assembly of surface mounted electronic components, wherein the molded plastic part of claim 12 is subjected to a process step including lead-free reflow soldering, wherein the molded plastic part is a plastic component for an electrical assembly.
